Effectiveness of integrated learning, problem-based learning, and direct learning models on HOTS in badminton - Sefri Hardiansyah; Nurlan Kusmaedi; Amung Ma'mun; Herman Subarjah; Syahriadi Syahriadi; Deddy Rahmat Saputra (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: Higher-Order Thinking Skills (HOTS) are needed by students in higher education as a provision for them to enter the world of work, therefore it is important for every student to master HOTS well, including physical education students at Universitas Negeri Padang.